Bacterial Physiological Adaptations to Contrasting Edaphic Conditions Identified Using Landscape Scale Metagenomics - Ashish A. Malik (American Society for Microbiology, 2017)
ABSTRACT Environmental factors relating to soil pH are important regulators of bacterial taxonomic biodiversity, yet it remains unclear if such drivers affect community functional potential. To address this, we applied whole-genome metagenomics to eight geographically distributed soils at opposing ends of a landscape soil pH gradient (where “low-pH” is ~pH 4.3 and “high-pH” is ~pH 8.3) and evaluated functional differences with respect to functionally annotated genes. First, differences in taxonomic and functional diversity between the two pH categories were assessed with respect to alpha diversity (mean sample richness) and gamma diversity (total richness pooled for each pH category). Low-pH soils, also exhibiting higher organic matter and moisture, consistently had lower taxonomic alpha and gamma diversity, but this was not apparent in assessments of functional alpha and gamma diversity. However, coherent changes in the relative abundances of annotated genes between low- and high-pH soils were identified; with strong multivariate clustering of samples according to pH independent of geography. Assessment of indicator genes revealed that the acidic organic-rich soils possessed a greater abundance of cation efflux pumps, C and N direct fixation systems, and fermentation pathways, indicating adaptations to both acidity and anaerobiosis. Conversely, high-pH soils possessed more direct transporter-mediated mechanisms for organic C and N substrate acquisition. These findings highlight the distinctive physiological adaptations required for bacteria to survive in soils of various nutrient availability and edaphic conditions and more generally indicate that bacterial functional versatility with respect to functional gene annotations may not be constrained by taxonomy. IMPORTANCE Over a set of soil samples spanning Britain, the widely reported reductions in bacterial taxonomic richness at low pH were found not to be accompanied by significant reductions in the richness of functional genes. However, consistent changes in the abundance of related functional genes were observed, characteristic of differential ecological and nutrient acquisition strategies between high-pH mineral soils and low-pH organic anaerobic soils. Our assessment at opposing ends of a soil gradient encapsulates the limits of functional diversity in temperate climates and identifies key pathways that may serve as indicators for soil element cycling and C storage processes in other soil systems. To this end, we make available a data set identifying functional indicators of the different soils; as well as raw sequences, which given the geographic scale of our sampling should be of value in future studies assessing novel genetic diversity of a wide range of soil functional attributes.